Nos Que Aqui Estamos por Vos Esperamos. Approaches Between Cinema and History - Sosa-Vota, M (UNIV FED RIO DE JANEIRO, FAC LETRAS, 2020)
The main objective of this article is to think about the possibilities of the documentary film regarding to the past representation and the contemporary absence of what it was present, time ago, from de movie directed by the Brazilian Marcelo Masagao, Nos que aqui estamos por vos esperamos (1999). It is considered that history does not have the monopoly of the representations of the past. Documentary films can be understood as a way of historical explanations and interpretations of the past. They explain and communicate facts of the past form a particular language, different form the one used by history.